2018
DOI: 10.1186/s12906-018-2320-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of Euphorbia supina on Propionibacterium acnes-induced skin inflammation in vitro and in vivo

Abstract: BackgroundEuphorbia supina (ES) plant has been used as treatment for inflammatory conditions. The antibacterial effect and the anti-inflammatory mechanism of ES for Propionibacterium (P.) acnes-induced inflammation in THP-1 cells and acne animal model remain unclear. Therefore, the objective of the present study was to determine the antibacterial and anti-inflammatory activities of ES against P. acnes, the etiologic agent of skin inflammation.MethodThe antibacterial activities of ES were tested with disc diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…However, the effect was only observed at the highest dose tested. These results agree with previous findings 13 , 18 , as the in vivo skin-penetration properties and activity of PCA against C. acnes were dose-dependent, suggesting that higher concentrations of topical PCA may be required to achieve antimicrobial activity against this organism in living skin.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, the effect was only observed at the highest dose tested. These results agree with previous findings 13 , 18 , as the in vivo skin-penetration properties and activity of PCA against C. acnes were dose-dependent, suggesting that higher concentrations of topical PCA may be required to achieve antimicrobial activity against this organism in living skin.…”
Section: Discussionsupporting
confidence: 92%
“…Liu et al demonstrated the efficacy of PCA derived from Roselle calyx against the drug-resistant organisms MRSA, Klebsiella pneumoniae, and P. aeruginosa 26 . Lim et al demonstrated the antibacterial activity of PCA in Euphorbia supina against C. acnes 18 . Our findings agree, as saturation with PCA resulted in clear zones of inhibition against C. acnes (22 mm), S. aureus (8 mm), MRSA (9 mm), and P. aeruginosa (10 mm).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, the conditional pathogen C. acnes generally cause a self‐limiting infection, which is not easy to mimic (Lim et al, 2018; Sivasankar et al, 2016). In 2013, a mouse model of chronic prostatic inflammation induced by C. acnes was developed using C57BL/6J mice, but it was preclinical and took 8 weeks for the entire observation (Shinohara et al, 2013).…”
Section: Discussionmentioning
confidence: 99%